Problems in Arranging the Position of Special Staff of the Special Region of Jakarta Government Reviewed from Law Number 2 of 2024 Concerning Special Provinces and Law Number 20 of 2023 Concerning State Civil Apparatus - Putra, Budayawan Gerio (Journal of Current Research In Multidisciplinary, 2025)
On Wednesday, February 5, 2025, the Head of the State Civil Service Agency (BKN) of the Republic of Indonesia issued a strong warning to newly elected regional heads for the 2025–2030 term regarding the appointment of new personnel, particularly special staff. Prof. Zudan emphasized that appointing new staff must follow the legal recruitment path, namely through the State Civil Apparatus (ASN) and Government Employees with Work Agreements (PPPK), as regulated in Law No. 20 of 2023 on the State Civil Apparatus. However, the Governor of the Jakarta Special Region, Pramono Anung, asserted that Jakarta has special characteristics that allow the appointment of special staff. In accordance with Law No. 2 of 2024, which governs the Special Region of the Province of Jakarta, and based on the principle of lex superior derogat legi generali, the higher regulation overrides the general law. Article 38 paragraphs (1) and (2) of Law No. 2 of 2024 explicitly state that the Governor has the authority to appoint special staff, with detailed provisions regarding the requirements, appointment procedures, and remuneration to be regulated through a Governor Regulation.